Promoting collaborative governance to integrated halal tourism development in Bukittinggi city, Indonesia - Yvanka, Vika; Erianjoni, Erianjoni (Otoritas : Jurnal Ilmu Pemerintahan, 2024)
This study addresses the potential of halal tourism as a promising revenue sector in Bukittinggi City, which has a majority Muslim population with the philosophy of life “Adat Basandi Syarak, Syarak Basandi Kitabullah.” Bukittinggi was chosen as a tourism destination based on its strong local culture, customs, and religion, which are aligned with the vision of halal tourism. Bukittinggi City has potential, but also has to face problems including limited infrastructure, halal tourism awareness, and contention over the socio-cultural impact of the arrival of foreign travelers. This research uses a qualitative method with an explanatory approach and data collection through participant observation, in-depth interviews, and documentation studies. The results of this study indicate that the community, tourism businesses, and the government contribute to integrating halal tourism development in Bukittinggi City by providing services, regulations, supervision, training, socialization, assistance, capacity building, and promotion of halal tourism. An active collaboration is also required to ensure inclusive, authentic, and sustainable growth of the tourism industry, which makes Bukittinggi a desirable halal tourism destination for Muslim visitors from all over the world. Moreover, the effective implementation of collaboration strategies between the local government, business actors, and local communities is expected to increase local economic growth and tourism image.